Risk management in the energy sector: Challenges, strategies, and regulatory frameworks in Western Balkans as Albania case study - Hyna, Eva; Vyshka, Eli (BIORE Scientia Academy, 2025)
The energy sector, characterized by substantial capital investments, long-term projects, volatile commodity prices, and increasing environmental concerns, faces a complex and evolving landscape of risks (Kaarle Parikka, 2024). This article examines the key challenges in effective risk management within this critical sector, ranging from operational disruptions and geopolitical instability to the impacts of the energy transition and climate change. It explores diverse risk management strategies employed by energy companies, including advanced forecasting techniques, hedging instruments, diversification, and robust emergency response plans. Furthermore, the paper analyzes the crucial role of regulatory frameworks at national and international levels in shaping risk management practices and promoting resilience across the energy value chain in Western Balkans having Albania as case study. By synthesizing current trends and best practices, this article provides valuable insights for energy stakeholders seeking to navigate uncertainty and ensure sustainable and secure energy supply.